Differential expression of apoptosis-related genes from death receptor pathway in chronic myeloproliferative diseases. Issue 1 (2nd November 2010) - Tognon, Raquel; Gasparotto, Elainy Patrícia Lino; Leroy, Janine Marie Gisele; Oliveira, Gislane Lelis Vilela; Neves, Renata Peres; Carrara, Rita de Cássia Viu; Kashima, Simone; Covas, Dimas Tadeu; Santana, Mary; Souto, Elizabeth Xisto; Zanichelli, Maria Aparecida; Velano, Carlos Eduardo Engel; et al.
Abstract : Background: Chronic myeloproliferative disorders (MPDs) are clonal haematopoietic stem cell malignancies characterised by an accumulation of mature myeloid cells in bone marrow and peripheral blood. Deregulation of the apoptotic machinery may be associated with MPD physiopathology. Aims: To evaluate expression of death receptors' family members, mononuclear cell apoptosis resistance, and JAK2 allele burden. Subjects and Methods: Bone marrow haematopoietic progenitor CD34 cells were separated using the Ficoll-hypaque protocol followed by the Miltenyi CD34 isolation kit, and peripheral blood leukocytes were separated by the Haes-Steril method. Total RNA was extracted by the Trizol method, the High Capacity Kit was used to synthesise cDNA, and real-time PCR was performed using SybrGreen in ABIPrism 7500 equipment. The results of gene expression quantification are given as 2 −ΔΔCt . The JAK2 V617F mutation was detected by real-time allelic discrimination PCR assay. Peripheral blood mononuclear cells (PBMCs) were isolated by the Ficoll-hypaque protocol and cultured in the presence of apoptosis inducers. Results: In CD34 cells, there was mRNA overexpression for fas, faim and c-flip in polycythaemia vera (PV), essential thrombocythaemia (ET) and primary myelofibrosis (PMF), as well as fasl in PMF, and dr4 levels were increased in ET. In leukocytes, fas, c-flip and trail levels were increased in PV, and dr5 expression was decreased in ET. There was an association between dr5 and fasl expression and JAK2V617F mutation. PBMCs from patients with PV, ET or PMF showed resistance to apoptosis inducers. Conclusions: The results indicate deregulation of apoptosis gene expression, which may be associated with MPD pathogenesis leading to accumulation of myeloid cells in MPDs.